THE EFFECT OF WORKING CAPITAL ROUND, SALES GROWTH AND LIQUIDITY ON CORPORATE PROFITABILITY: Case Study of food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018 - Elsye Fatmawati (Journal of Research in Business, Economics, and Education, 2019)
The development of this industry is inseparable from the population of Indonesia which continues to grow each year. As the population grows, the volume of demand for consumption products also increases. In addition, food and beverage companies will continue to exist and are most resistant to crisis conditions compared to other sectors. The formulation of the problem in this study is to find out whether working capital turnover, sales growth and liquidity can affect company profitability. And the purpose of this study is to determine the effect of each variable working capital turnover, sales growth and liquidity on the profitability variable. The research data was collected using quantitative methods. The data source used in this study was secondary data sources in the form of corporate financial reporting documents. The population used by researchers was the Consumer Goods Industry Sector Company which was listed on the Indonesia Stock Exchange in the 2014-2018 period, which obtained 14 companies and using purposive sampling technique. The analysis in this study uses Descriptive Statistics, Panel Data Regression Analysis, Classical Assumption Test and Hypothesis Test with Eviews 10 application.